Analysis of Dispersed Phase of Coconut Milk Emulsion - Hudiyanti, Dwi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2000)
Experiments were conducted to study the dispersed phase of coconut milk emulsion. They were optical microscopy analysis using a Nikon Microscope and particle size analysis using a Coulter Counter Multisizer. Particle size analysis using a Coulter Counter Multisizer on both original coconut milk and homogenized coconut milk at T = 19 Â°C indicated that they had a wide range of particle size with average value of 5.988 + 1 .0 pm and 6.696 + 1 . 1 pm in diameter respectively. Optical microscopy analysis showed that homogenization of coconut milk after it was heated in a water bath at T = 35 Â°C for about 15 minutes resulted in changes of particle size, the particle size became smaller. The result lead to a conclusion that the coconut milk emulsion may be considered as a polydisperse emulsion and it indicates that the system should not be sensitive to small variations in preparation or subsequent handling.